Phylogenetic diversity of bacterial communities in bovine rumen as affected by diets and microenvironments - Kim, Minseok; Morrison, Mark; Yu, Zhongtang (Folia microbiologica, 2011)
Phylogenetic analysis was conducted to examine ruminal bacteria in two ruminal fractions (adherent fraction vs. liquid fraction) collected from cattle fed with two different diets: forage alone vs. forage plus concentrate. One hundred forty-four 16S rRNA gene (rrs) sequences were obtained from clone libraries constructed from the four samples. These rrs sequences were assigned to 116 different operational taxonomic units (OTUs) defined at 0.03 phylogenetic distance. Most of these OTUs could not be assigned to any known genus. The phylum Firmicutes was represented by approximately 70% of all the sequences. By comparing to the OTUs already documented in the rumen, 52 new OTUs were identified. UniFrac, SONS, and denaturing gradient gel electrophoresis analyses revealed difference in diversity between the two fractions and between the two diets. This study showed that rrs sequences recovered from small clone libraries can still help identify novel species-level OTUs.
Keywords: krmivo pro zvířata; Polymorphism, Restriction Fragment Length; Phylogeny; RNA, Ribosomal, 16S; skot; genomová knihovna; Bacteria; Rumen; zvířata; Sequence Analysis, DNA; Animal Feed; RNA ribozomální 16S; Cattle; bachor; Genomic Library; ribotypizace; Biodiversity; polymorfismus délky restrikčních fragmentů; Ribotyping; biodiverzita; sekvenční analýza DNA; Animals; Microbial Consortia; fylogeneze; mikrobiální společenstva